Effects of pile driving on Bangkok clay - Surachai Sasisuwan; Chai Muktabhant; Brand, E.W.; Moh, Za-Chieh; Asian Institut e of Technology (Bangkok : Asian Institute of Technology, 1972)
Two piles were driven to study the effects of pile driving on shear strength and pore water pressure. The piles were steel piles 50 cm. in diameter and 12 m. in embedded length. Two bore holes were made before the first pile (P1 ) was driven to study the undisturbed soil properties and eight bore holes were made afterward to study the thixotropic strength regain and the extent of disturbance. The undrained shear strength was measured by field vane shear, unconfined compression and triaxial (UU) tests.. Twelve piezometers were installed prior to the second pile CP2 ) was driven to study the effect of pile driving on pore water pressure. Results of the investigations revealed that the soil around the pile was disturbed to about one pile diameter from the pile surface. The strength close to the pile (0.3 d), measured the same day as pile driving, was much reduced due to disturbance caused by piling. All the lost strengths were regained within 14 days of resting. Very high pore pressure was recorded close to the pile in the region of local shear failure at different times after pile driving. Most of the excess pore pressures have dissipated within one month.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1972
Keywords: Piling (Civil engineering)